Simplify the following expression using PEMDAS
6 + 3 x 42 – 7 PLEASE SHOW THE DIFFERENTS STEPT

Question|Rated good

Asked 2/20/2011 4:59:02 PM

Updated 5/31/2014 4:54:24 PM

1 Answer/Comment

f
freestar.config.enabled_slots.push({ placementName: 'weegy_incontent_1', slotId: 'weegy_incontent_1' });

Expert answered|ambrosio_09|Points 1025|

Expert answered|ambrosio_09|Points 1025|

Expert answered|ambrosio_09|Points 1025|

Question|Rated good

Asked 2/20/2011 4:59:02 PM

Updated 5/31/2014 4:54:24 PM

1 Answer/Comment

Rating

8

3 + 4[(8 ÷ 2) + 3];

3 + 4[4 + 3];

3 + 4[7];

3 + 28 = 31

3 + 4[4 + 3];

3 + 4[7];

3 + 28 = 31

Added 5/31/2014 4:54:24 PM

This answer has been confirmed as correct and helpful.

4x + 18 = 10 User: 12x – 17 = -41 **Weegy:** 12x-17=-41 (add 17 to both sides), (More)

Question

Expert Answered

Updated 12/28/2018 10:22:07 AM

3 Answers/Comments

4x + 18 = 10

4x = 10 - 18

4x = -8

x = -8/4

x = -2

4x = 10 - 18

4x = -8

x = -8/4

x = -2

Added 8/16/2015 5:57:12 AM

This answer has been confirmed as correct and helpful.

12x – 17 = -41

12x = -41 + 17

12x = -24

x = -24/12

x = -2

12x = -41 + 17

12x = -24

x = -24/12

x = -2

Added 8/16/2015 5:57:41 AM

This answer has been confirmed as correct and helpful.

Let's solve your equation step-by-step.

12x 17= 41

Step 1: Add +17 to both sides.

12x 17+17= 41+17

12x= 24

Step 2: Divide both sides by 12.

12x12= 24

12x= 2

Answer:

x= 2

12x 17= 41

Step 1: Add +17 to both sides.

12x 17+17= 41+17

12x= 24

Step 2: Divide both sides by 12.

12x12= 24

12x= 2

Answer:

x= 2

Added 12/28/2018 10:22:07 AM

Simplify the following expressions using PEMDAS 6 + 3 x 42 – 7 Please show steps with answer.

Question

Updated 6/1/2014 11:46:09 AM

1 Answer/Comment

6 + 3 x 42 – 7;

6 + 126 - 7;

132 - 7 = 125

6 + 126 - 7;

132 - 7 = 125

Added 6/1/2014 11:46:09 AM

This answer has been confirmed as correct and helpful.

PLEASE USE THE P.E.M.D.A.S TO SIMPLIFY THIS PROBLEM: 6 + 3 x 42 – 7 **Weegy:** 6 + 3 x 42 – 7; = 6 + 126 -7; = 125
(More)

Question

Expert Answered

Updated 5/31/2014 4:55:04 PM

0 Answers/Comments

Simplify: 4(3 – x) – 3(-5 – 12x)

Question

Updated 12/29/2018 8:50:18 PM

2 Answers/Comments

4(3 – x) – 3(-5 – 12x)

= 12 - 4x + 15 + 36x

= 32x + 27

= 12 - 4x + 15 + 36x

= 32x + 27

Added 5/14/2018 11:48:39 AM

This answer has been confirmed as correct and helpful.

Solve by using PEMDAS: 6 X 3 + 10/2. **Weegy:**
6 X 3 + 10/2
= 18 + 10/2
= 18 + 5
= 23
(More)

Question

Expert Answered

Updated 7/16/2014 11:03:21 AM

1 Answer/Comment

36,642,919

questions answered

There are no comments.